Rural People’s Attitudes Towards Voting Rights in Bangladesh:: A Study on Savar and Saturia Upazila - Islam, Shahidul; Alam, Md. Shamsul (The Jahangirnagar Review, 2025)
The study focuses on how rural people in Bangladesh are aware of voting rights which is an important aspect for sustaining democracy. It analyzes responses from 200 respondents in Savar and Saturia Upazila to examine awareness by age, gender, education, income and those based in the media. The results indicate that most respondents know their right to vote, but have large gaps in knowledge of constitutional and legal guarantees. Knowledge levels are also widely varying, with younger, educated and higher income having higher awareness. Awareness is shown to be significantly influenced by media usage. Socioeconomic barriers limit rural women, laborers and low-income groups to understanding. Moreover, misconceptions about the candidacy process, and systemic influences, such as constraints from a lack of the financial means, limit wider political participation. This study highlights the importance of targeted awareness campaign to fill these gaps as education and media help to foster educated electoral involvement. The implication of these findings is that the strengthening of democratic practice calls for additional new challenges and opportunities in emerging democracies such as rural Bangladesh.